Design and performance of a 16-channel radiation-hardened low-noise front-end readout ASIC for CZT-based hard X-ray imager. (February 2016) - Gao, W.; Li, X.; Liu, H.; Hu, Y.
Abstract: This paper presents the design and the performance of a low-noise front-end readout application specific integrated circuit (ASIC) dedicated to CZT detectors for a hard X-ray imager. A cascode amplifier based on split-let topology is proposed to realize the charge-sensitive amplifier (CSA) for the sake of a single positive power supply. A leakage-current-compensation circuit is added to suppress the maximum leakage current of 10 nA. The output of the CSA is connected to a CR–RC shaper. In the timing branch, the output of the CSA is followed by a fast shaper for the trigger acquisition. A digital monostable circuit is designed to adjust the delay of trigger signals so that the peak value of the shaped voltage signals can be tracked. The sampled voltages are stored into an analog memory. A radiation-hardened-by-design methodology is proposed to achieve the radiation hardness for the space applications. A 16-channel front-end readout ASIC is designed and implemented in TSMC 0.35 μm CMOS process. The die size is 2.12 mm×4.60 mm. The input range of the ASIC is from 4k e − to 140k e −, which is suitable for the detection of the gamma ray from 20 keV to 650 keV. The ASIC has been tested. The gain of the readout channel is typically 81.4 mV/fC. The equivalent noise charge (ENC) is 50 e − at zero farad plus 18 e − per picofarad. The nonlinearity is less than 3%. The crosstalk is less than 2%. The static power dissipation is about 16.5 mW plus 10.6 mW/channel. In addition, the tested results show that the proposed ASIC can resist larger than 200 krad(Si) TID irradiation.